Complete mitochondrial genomes for three lizards (Anolis punctatus, Sceloporus woodi, and S. grammicus): a contribution to mitochondrial phylogenomics of Iguanoidea - Ana Teresa Nogueira Dumans; Gabriela Warwar Teixeira; Gabriel Alves Vieira; Deise Schroder Sarzi; Carolina Furtado; W. Bryan Jennings; Francisco Prosdocimi (Mitochondrial DNA. Part B. Resources, 2019)
The complete mitochondrial genomes of the Spotted Anole (Anolis punctatus), Florida Scrub Lizard (Sceloporus woodi), and Mesquite Lizard (S. grammicus) were assembled and annotated. Genomic DNA of A. punctatus was sequenced in one-sixth of a lane in an Illumina HiSeq while comparable sequencing data for S. woodi and S. grammicus were retrieved from the Short Read Archive (entries SRR1286259 and SRR1145766, respectively). We assembled these mitogenomes using MIRA, NovoPlasty, and/or MITObim software. The resulting whole and circularized mitogenome assemblies exhibited typical vertebrate sequence length and gene organization. We deposited these mitogenomes into public databases under accession numbers MK091854, BK010487, and BK010486, respectively. To verify the taxonomic identifications of our mitogenomes (as iguanian lizards), we conducted maximum likelihood analyses with 14 published mitogenomes from the lizard superfamily Iguanoidea and two outgroups. Our analysis of concatenated gene sequences from mitochondria confirmed the taxonomic identities of our mitogenomes to the genus level.